MLPA method for PMP22 gene analysis - Stangler Herodež, Špela (Acta chimica slovenica, 2005)
DNA copy number alterations are responsible for several categories of human diseases and syndromes. These changes can be detected by cytogenetic studies when there is involvement of several kilobases or megabases of DNA. Examination of sub-microscopic changes is possible by using short probes flanked by the same primer pairs. Multiplex ligation-dependent probe amplification (MLPA) is a simple, high resolution method by which not sample nucleic acids but probes added to the samples are amplified and quantified. Charcot-Marie-Tooth disease type 1A (CMT1A) is the most common inherited peripheral neuropathy with a prevalence of about 1/10000. By a gene dosage mechanism, commonly trisomic overexpression of PMP22 results in CMT1A whereas its monosomic underexpression causes hereditary neuropathy with liability to pressure palsies (HNPP). We applied MLPA to the PMP22 gene in order to develop an efficient and sensitive test for detecting these gene dosage changes. The method was used on 56 samples collected for a previous comparative study on routine methods for CMT1A diagnosis used in our laboratory. All diagnoses agreed with results from other methods. The MLPA PMP22 assay is a simple, fast and accurate screening test for molecular diagnosis of CMT1A and HNPP.
Keywords: Charcot-Marie-Tooth disease; Charcot-Marie-Toothova bolezen; Citogenetska analiza; Cytogenetic analysis; DNA; genske analize; MLPA